2021
DOI: 10.1177/08850666211045626
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neutrophil-Lymphocyte Count Ratio in COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background: The neutrophil–lymphocyte count ratio (NLR) has emerged as a potential prognostic tool for different diseases. In the current coronavirus disease (COVID-19) pandemic, the NLR may be a useful tool for risk scarification and the optimal utilization of limited healthcare resources. However, there is no consensus regarding the optimal value of NLR, and the association with disease severity and mortality. Thus, this study aims to systematically analyze the current evidence of the utility of baseline NLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 121 publications
4
41
1
6
Order By: Relevance
“…We found that in 2020-year patients' age, gender, presence of CKD, COPD, fever, increase in NLR, and decrease in oxygen saturation had significant predictive value for COVID-19 severity. The data obtained are consistent with numerous results of other works were shown the predictive value of age [16], gender [17], comorbidity [18][19][20], clinical symptoms of disease [21], and increase of NLR [22] for the prognosis of severity and death.…”
Section: Discussionsupporting
confidence: 91%
“…We found that in 2020-year patients' age, gender, presence of CKD, COPD, fever, increase in NLR, and decrease in oxygen saturation had significant predictive value for COVID-19 severity. The data obtained are consistent with numerous results of other works were shown the predictive value of age [16], gender [17], comorbidity [18][19][20], clinical symptoms of disease [21], and increase of NLR [22] for the prognosis of severity and death.…”
Section: Discussionsupporting
confidence: 91%
“…Meta-analyzes also shows that the NLR can be a good marker of disease severity and has predictive value for the outcome. The limit cannot be clearly established, but a severe case above 4.5 seems to be expected ( 16 , 17 ). Elmaradny and colleagues studied the relationship between NLR and preeclampsia.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, elevated NLR values on hospital admission are linked to mortality and severity of COVID‐19. 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, a previous review and meta‐analysis highlighted the NLR as an imperative marker of prognosis for patients with COVID‐19. In addition, elevated NLR values on hospital admission are linked to mortality and severity of COVID‐19 44,45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation